Strategi Pengembangan Lumpur Lapindo Sebagai Wisata Edukasi Di Kabupaten Sidoarjo Jawa Timur - Rizky Maulana Abdillah; Ida Bagus Suryawan (JURNAL DESTINASI PARIWISATA, 2019)
Sidoarjo has a unique tourist attraction due to the disaster that has happened before, so that emerging potential that can be developed into tourist attraction. But Lapindo mud tourism has a very complex problematics to be used as a tourist attraction. Therefore, it aims to develop lapindo mud as a tourist attraction in Porong district East Java by knowing its development strategy. This research was conducted in Porong district by conducting interviews to selected stakeholders using purposive sampling method. Data is gathered through deep interviews with the tourism department and local communities, then in analysis using SWOT analysis. The results of this study are: 1) potential livelihood opportunities undergo changes to the aspects of tourism. 2) aspects in the attraction of this lapindo mud tourism is very minimal because there is still not much development done by the Government of Sidoarjo and by the manager in the tourist attraction Lapindo mud. 3) The development strategy of Lapindo mud as a tourist attraction has more opportunities because the community began to feel changes in the livelihood because of the many tourists visiting the Lapindo mud, but the lack of Public facilities for tourists visiting the attraction. It can be concluded that the consequences of Lapindo mud disaster can be developed as a tourist attraction because it provides opportunities for local communities such as obtaining new livelihoods. E. Keywords : Development, Strategy, Tourist Attraction, MUD Lapindo